Absorption, metabolism, and excretion of the antiemetic rolapitant, a selective neurokinin-1 receptor antagonist, in healthy male subjects - Zhang, Zhi-Yi; Wang, Jing; Kansra, Vikram; Wang, Xiaodong (Investigational new drugs, 2019)
Summary Rolapitant is a neurokinin-1 receptor antagonist that is approved in combination with other antiemetic agents in adults for the prevention of delayed nausea and vomiting (CINV) associated with initial and repeat courses of emetogenic cancer chemotherapy, including but not limited to highly emetogenic chemotherapy. Here, we assessed the absorption, metabolism, and excretion of 14 C-labeled rolapitant in healthy male subjects. Rolapitant was administered as a single 180-mg oral dose containing approximately 100 μCi of total radioactivity, with plasma, urine, and fecal samples collected at defined intervals after dosing. Rolapitant had a large apparent volume of distribution, indicating that it is widely distributed into body tissues. Rolapitant was slowly metabolized and eliminated with a mean half-life of 186 h. Exposure to the major metabolite of rolapitant, C4-pyrrolidinyl hydroxylated rolapitant or M19, was approximately 50% of rolapitant exposure in plasma. Renal clearance was not a significant elimination route for rolapitant-related entities. Total radioactivity recovered in urine accounted for 14.2% of the dose, compared to 72.7% recovery in feces. Adverse events (AEs) were generally mild; there were no serious AEs, and no clinically significant changes in laboratory or electrocardiogram parameters were observed. The combination of rolapitant safety, its long half-life, extensive tissue distribution, and slow elimination via the hepatobiliary route (rather than renal excretion) suggest suitability that a single dose of rolapitant may provide protection against CINV beyond the first 24 h after chemotherapy administration.